Automatic Watering With Solar Panel Power Support Using Arduino - Fitrianta Eka Saputra, Rahmad; Noor Prawita, Fathah (eProceedings of Applied Science, 2023)
Abstract— Most of the irrigation systems in Indonesia use a manual system. Farmers have to open and close irrigation channels to the rice fields conventionally. An intelligent automatic rice field irrigation system powered by solar panels using an Arduino microcontroller based on the Internet of Things (IoT) is a tool made to help farmers make it easier to drain water into their fields remotely in real time. This tool aims to increase the effectiveness of farmers' work. This tool is expected to facilitate the farmers work. The hardware used as a portal is to use a servo motor to retrieve water level data using a soil moisture sensor and as a control center using a NodeMCU ESP8266 microcontroller. In the irrigation portal control system, control is carried out using an android application thats connected to the controller node via the apy key from web hosting, after the portal is opened the soil moisture data from the controller node is sent and displayed in the application. The system control process can be done anywhere and anytime as long as it is connected to the internet in real time. This system uses power support from solar panels to produce a battery energy source.Keywords— intelligent system, soil moisture, irrigation, internet of things